Exploring the Process of Preservice Teachers’ Diagnostic Activities in a Video-Based Simulation - Codreanu, Elias; Sommerhoff, Daniel; Huber, Sina; Ufer, Stefan; Seidel, Tina (Frontiers in Education, 2021)
Formative assessment of student learning is a challenging task in the teaching profession. Both teachers’ professional vision and their pedagogical content knowledge of specific subjects such as mathematics play an important role in assessment processes. This study investigated mathematics preservice teachers’ diagnostic activities during a formative assessment task in a video-based simulation. It examined which mathematical content was important for the successful assessment of the simulated students’ mathematical argumentation skills. Beyond that, the preservice teachers’ use of different diagnostic activities was assessed and used as an indicator of their knowledge-based reasoning during the assessment situation. The results showed that during the assessment, the mathematical content focused on varied according to the level of the simulated students’ mathematical argumentation skills. In addition, explaining what had been noticed was found to be the most difficult activity for the participants. The results suggest that the examined diagnostic activities are helpful in detecting potential challenges in the assessment process of preservice teachers that need to be further addressed in teacher education. In addition, the findings illustrate that a video-based simulation may have the potential to train specific diagnostic activities by means of additional instructional support.